The Influence of Multimedia on Students’ Religious Character in the Learning of Islamic Religious Education - Ediansyah, Ediansyah (Yayasan Sembilan Pemuda Indonesia, 2022)
The purpose of this study was to determine the effect of multimedia on the religious character of students in learning Islamic Religious Education in class VII SMP Negeri 2 Bengkulu Utara. This type of research is quasi-experimental research, the research method used in this study is quantitative. The data collection techniques used by researchers are questionnaires, observation sheets, and documentation. In this study there are two variables, namely Variable X (Multimedia Influence) and Variable Y (Religious Character). The research population was all students of class VII, totaling 147 students, from class VII.A to class VII.E and the sample of this study, 31 students of class VII.C as the control class and 27 students of class VII.E as the experimental class. The research results that there is influence of multimedia on the religious character of students in learning Islamic Religious Education in class.